God's pursuit of man eaudiobook The divine conquest of the human heart. - Tozer, A.W (christianaudio, 2006)
This book formerly titled The DIVINE CONQUEST, was written as a sequel to THE PURSUIT OF GOD. Admitting to having been forced by inward pressure and an unbearable burden to write it, Tozer's aim was to assure believers that if they want to know the power of Christ they must be invaded by God. "This little book of the spiritual way has not been 'made' in any mechanical sense, it has been born out of inward necessity....The sight of the languishing church around me and the operations of a new spiritual power within me have set up a pressure impossible to resist." —A.W. Tozer